Design of Eco pedagogic Models in Preserving Local Wisdom Values - Fatahidin, Rijal (International Conference on Elementary Education, 2021)
The entry and development of Science and Technology today has exploded the industrial revolution movement which tends to lead to a pattern of needs that depend on the industry, import, packaging, and long-distance transportation. This trend cannot be denied that it can lead to various new problems that lead to environmental destruction and loss of the value of a community's local wisdom. This includes the areas around us which are potential industrial zones in Indonesia, which are vital objects for local and global investors in the establishment of large companies in various sectors. This can be seen from the high and still alarming level of natural damage and is very detrimental to the people and ecosystems that live in it, people who stick to preserving Local Wisdom Values are increasingly disappearing, while nature is very important in providing benefits to the surrounding community. This is exacerbated by the tendency of our society to interpret education as a mere trajectory of the future, meaning that it is oriented towards fulfilling jobs in factories. Based on these problems, it is necessary to have a strategic effort to design a new paradigm to realize an educational model that emphasizes the value of cultural wisdom or is based on Local Wisdom Values, as well as efforts to build critical attitudes, awareness, and local intelligence in understanding various life phenomena that are detrimental to the environment through a design-build an Eco pedagogic Models to create future expectations of society for the environment.